THE INFLUENCE OF INCOME AND INTEREST ON KPR DECISIONS WITH FINANCIAL LITERACY AS A MODERATING VARIABLE - Nuraini Nuraini; Juliani Pudjowati; Eva Purnamasari; Endang Wulandari; Heri Sasono (ITB AAS Indonesia Surakarta, 2024)
Abstract Housing is a primary need that every individual dreams of having. Individuals who cannot afford to buy a house in cash choose the mortgage route so they can occupy it and ultimately own it when the installments are finished. There are a number of factors that can influence consumers to decide on a mortgage, including individual income and home mortgage interest rates. Therefore, this research aims to analyze the influence of the Income and Interest Rate variables on the KPR Decision variable. Different from previous studies, this research adds the Financial Literacy variable which researchers believe can strengthen the influence of the Income and Interest Rate variables on the KPR Decision variable. This research is quantitative research with an explantory approach that develops research (Sukmawati, 2020). The data used in this research is primary data distributed to 250 BSI bank customers who have been offered KPR throughout Indonesia. The research results show that the Income and Interest Rate variables have a positive relationship and have a significant influence on KPR decisions. Apart from that, the Financial Literacy variable can moderate the influence of the Income and Interest Rate variables on the KPR Decision variable. Keywords: Income, Interest, Financial Literacy, KPR Decision